Reduced time at customs through implementing the Trade Facilitation Agreement (TFA) would be a significant boost to intra-African trade for AfCFTA countries - Jaime De Melo; Zakaria Sorgho; Laurent Wagner (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
All WTO members participate in the Trade Facilitation Agreement (TFA), a rules-based bottom-up approach built on monitorable provisions (e.g. the publication of information, advance rulings, appeal or review of decisions, transparency, and border agency cooperation) aimed at reducing time in customs. The paper draws on the OECD indicators of the state of implementation of provisions in the TFA summarized in a TFI (Trade Facilitation Index). to estimate the reduction in waiting-time at customs for a large sample of 160 countries. Implementing the TFA could be a significant complement to the AfCFTA's objectives. The paper's estimates suggest that a realistic implementation of TFA measures could reduce time in customs for imports by 3.7 days and by 1.9 days for exports. Using extraneous estimates from customs-level transactions, this translates to a reduction tariff Ad-Valorem Equivalent (AVE) in the range 3.5%-7% for imports and 8% extra growth of exports. The large differences in interests across AfCFTA participants–landlocked-coastal, resource-rich and resource-poor, large-small–suggest large gains from reducing tariffs on intra-African trade. However, tariff-reductions face the zero-sum hurdle of negotiations involving rent transfers across and within countries. By avoiding rent-transfer issues, this paper suggests that taking seriously the TFA provisions would be a powerful complement to the AcFTA's tariff-reduction agenda.
Keywords: F1; F13; F14; 330; International trade; trade policy; Trade Facilitation; LDCs; LLDCs; AFCFTA